2001
DOI: 10.1152/jn.2001.85.1.472
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of a Fast Persistent Inward Current in Action Potential Initiation and Control of Rhythmic Firing

Abstract: In spinal motoneurons in an in vivo preparation, we investigated the relationship between a fast persistent inward current located in or near the soma and the capacity of these cells to fire rhythmically. The fast persistent current could be markedly reduced by prolonged depolarization. Modest reductions resulted in profound changes in the slope of the frequency-current relationship. At greater reduction levels, rhythmic firing failed and could not be restored by increasing injected current. However, fully for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 18 publications
12
122
1
Order By: Relevance
“…It had previously been shown that phenytoin (Ն50 M) reduces the persistent sodium current in rat cortical neurons and enhances "slow adaptation" (Lampl et al 1998). In addition, it has been shown in cat spinal motoneurons that modest reductions in the persistent sodium current results in profound changes in the slope of the current-frequency relation and can lead to a failure of regular repetitive firing (Lee and Heckman 2001). Furthermore, based simply on the monotonic current-frequency relation of motoneurons, one would surmise that any agent or regimen that decreases a source of inward current should lead to lower firing rates (Powers and Binder 2001;Powers et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had previously been shown that phenytoin (Ն50 M) reduces the persistent sodium current in rat cortical neurons and enhances "slow adaptation" (Lampl et al 1998). In addition, it has been shown in cat spinal motoneurons that modest reductions in the persistent sodium current results in profound changes in the slope of the current-frequency relation and can lead to a failure of regular repetitive firing (Lee and Heckman 2001). Furthermore, based simply on the monotonic current-frequency relation of motoneurons, one would surmise that any agent or regimen that decreases a source of inward current should lead to lower firing rates (Powers and Binder 2001;Powers et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Progressive inactivation of these inward currents would be expected to result in a decreased firing rate. Whereas the low-threshold calcium current often shows facilitation rather than inactivation (Bennett et al 1998;Svirskis and Hounsgaard 1997), the persistent sodium current has been shown to undergo slow inactivation in neocortical neurons (Fleidervish et al 1996) and spinal motoneurons (Lee and Heckman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The PICs in motoneurons are composed of I NaP (Nishimura et al, 1989;Hsiao et al, 1998;Lee and Heckman, 2001;Li and Bennett, 2003;Powers and Binder, 2003;Tazerart et al, 2007) and calcium components (Schwindt and Crill, 1980;Hounsgaard and Kiehn, 1989;Heckman et al, 2008a;Carlin et al, 2009). PICs generating plateaus in motoneurons of adult cats (Hounsgaard et al, 1984), mice (Carlin et al, 2000b), rats (Li and Bennett, 2003), turtles (Hounsgaard and Mintz, 1988), and frogs (Perrier and Tresch, 2005) are predominantly mediated by L-type calcium channels and to a lesser extent by I NaP Harvey et al, 2006).…”
Section: Plateau Potentials Rely On I Canmentioning
confidence: 99%
“…It activates below the spike threshold with a time constant of the order of the millisecond (Crill, 1996). It amplifies synaptic inputs (Schwindt and Crill, 1995) and promotes spike initiation (Kuo et al, 2006), repetitive firing (Lee and Heckman, 2001;Harvey et al, 2006a), and bursting (Wu et al, 2005). It may also enhance subthreshold resonances (Gutfreund et al, 1995;Hutcheon et al, 1996;Hutcheon and Yarom, 2000).…”
Section: Introductionmentioning
confidence: 99%